Efficacy of fluoroscopy-guided endoscopic cricopharyngeal myotomy. Issue 12 (24th January 2019) - Fujiwara, K; Kawamoto, K; Taira, K; Fukuhara, T; Koyama, S; Kataoka, H; Kitano, H; Takeuchi, H
Abstract: Background: In endoscopic cricopharyngeal myotomy, surgeons sometimes have concerns about performing an adequate incision with only a narrow intra-cavital view from one direction. In order to overcome these issues, fluoroscopic radiography was used during endoscopic cricopharyngeal myotomy. Methods: Peri-operative fluoroscopic radiography was utilised to check the position of the diverticuloscope, and to confirm the extent of the incision during surgery. A balloon catheter was used to determine whether the cricopharyngeal muscle was sufficiently resected. Blood loss, peri-operative complications, and functional oral swallowing scale and penetration aspiration scale scores were evaluated. Results: In 12 out of 15 patients, intra-operative fluoroscopic radiography showed the diverticuloscope positioned in the post-cricoid area, and the cricopharyngeal muscle was raised and the surgery completed without adverse effect. Swallowing functions improved following surgery. Conclusion: Intra-operative fluoroscopy might improve endoscopic cricopharyngeal myotomy by allowing surgeons to confirm the extent of resection, and by reducing peri-operative morbidity and complication rates.